Can Statewide Emergency Department, Hospital Discharge, and Violent Death Reporting System Data Be Used to Monitor Burden of Firearm-Related Injury and Death in Rhode Island?. Issue 2 (March 2019) - Jiang, Yongwen; Ranney, Megan L.; Sullivan, Brian; Hilliard, Dennis; Viner-Brown, Samara; Alexander-Scott, Nicole
Abstract : Context: National data on the epidemiology of firearm injuries and circumstances of firearm deaths are difficult to obtain and often are nonreliable. Since firearm injury and death rates and causes can vary substantially between states, it is critical to consider state-specific data sources. Objective: In this study, we illustrate how states can systematically examine demographic characteristics, firearm information, type of wound, toxicology tests, precipitating circumstances, and costs to provide a comprehensive picture of firearm injuries and deaths using data sets from a single state with relatively low rates of firearm injury and death. Design: Cross-sectional study. Setting: Firearm-related injury data for the period 2005-2014 were obtained from the Rhode Island emergency department and hospital discharge data sets; death data for the same period were obtained from the Rhode Island Violent Death Reporting System. Main Outcome Measure: Descriptive statistics were used. Healthcare Cost and Utilization Project cost-to-charge ratios were used to convert total hospital charges to costs. Results: Most firearm-related emergency department visits (55.8%) and hospital discharges (79.2%) in Rhode Island were from assaults; however, most firearm-related deaths were suicides (60.1%). The annual cost of firearm-related hospitalizations was more than $830 000. Most decedents who died because of firearms tested positive for illicit substances. Nearly a quarter (23.5%) of firearm-related homicides were due to a conflict between the decedent and suspect. More than half (59%) of firearm suicide decedents were reported to have had current mental or physical problems prior to death. Conclusions: Understanding the state-specific magnitude and patterns (who, where, factors, etc) of firearm injury and death may help inform local injury prevention efforts. States with similar data sets may want to adopt our analyses. Surveillance of firearm-related injury and death is essential. Dissemination of surveillance findings to key stakeholders is critical in improving firearm injury prevention. States that are not part of the National Violent Death Reporting System (NVDRS) could work with their other data sources to obtain a better picture of violent injuries and deaths to make the best use of resources. Abstract : Supplemental Digital Content is Available in the Text.